An integrated non-targeted and targeted analysis approach for identification of semi-volatile organic compounds in indoor dust - Song, Zidong; Shi, Meng; Ren, Xiaopeng; Wang, Luyang; Wu, Yili; Fan, Yujie; Zhang, Yinping; Xu, Ying (Journal of hazardous materials, 2023)
Household dust contains a wide variety of semi-volatile organic compounds (SVOCs) that may pose health risks. We developed a method integrating non-targeted analysis (NTA) and targeted analysis (TA) to identify SVOCs in indoor dust. Based on a combined use of gas and liquid chromatography with high-resolution mass spectrometry, an automated, time-efficient NTA workflow was developed, and high accuracy was observed. A total of 128 compounds were identified at confidence level 1 or 2 in NIST standard reference material dust (SRM 2585). Among them, 113 compounds had not been reported previously, and this suggested the value of NTA in characterizing contaminants in dust. Additionally, TA was done to avoid the loss of trace compounds. By integrating data obtained from the NTA and TA approaches, SVOCs in SRM 2585 were prioritized based on exposure and chemical toxicity. Six of the top 20 compounds have never been reported in SRM 2585, including melamine, dinonyl phthalate, oxybenzone, diheptyl phthalate, drometrizole, and 2-phenylphenol. Additionally, significant influences of analytical instruments and sample preparation on NTA results were observed. Overall, the developed method provided a powerful tool for identifying SVOCs in indoor dust, which is necessary to obtain a more complete understanding of chemical exposures and risks in indoor environments. [Display omitted] •A non-targeted analysis workflow was developed with improved efficiency and reduced false discovery rates.•A total of 128 compounds were tentatively identified in standard dust, 113 of which had not been reported previously.•Integration of non-targeted and targeted analysis avoids the loss of critical trace compounds in indoor dust.•Prioritization of compounds based on exposure and chemical toxicity allows us to identify chemicals of concern.